PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN NUMERASI PESERTA DIDIK - Syafitri, Rafi; Muksar, Makbul; Sudirman, Sudirman (STKIP PGRI Situbondo, 2024)
This research is based on the low numeracy ability of grade IV students. The low numeracy ability of students is caused by (1) learning is still centered on the teacher, (2) practice questions are sourced from LKS books purchased from stores, (3) students are still weak in applying mathematical concepts to story problems. Based on these problems, the researcher developed a mathematics learning tool to improve the numeracy skills of grade IV students. The purpose of this study is to produce learning tools to improve the numeracy skills of grade IV students that are valid, effective, and efficient. The research method used in this development is the Plomp model which consists of three stages, namely (1) the initial research stage, (2) the prototype stage, and (3) the assessment stage. Hasil praktikalitas RPP dan LKPD memeroleh 93,8% dengan kategori sangat praktis. Sedangkan berdasarkan hasil uji skala kecil pada tes kemampuan numerasi diperoleh 92,5 % artinya perangkat pembelajaran matematika sangat efektif untuk meningkatkan kemampuan numerasi peserta didik kelas IV. Pada penelitian ini dapat disimpulkan bahwa perangkat pembelajaran matematika layak untuk dijadikan rujukan dalam pembelajaran matematika kelas IV SD.